Serum Soluble Mediator Profiles and Networks During Acute Infection With Distinct DENV Serotypes - Coutinho-da-Silva, Mikelly Santos; Sucupira, Pedro Henrique Ferreira; Bicalho, Kelly Alves; Campi-Azevedo, Ana Carolina; Brito-de-Sousa, Joaquim Pedro; Peruhype-Magalhães, Vanessa; Rios, Maria; Teixeira-Carvalho, Andréa; Coelho-dos-Reis, Jordana Grazziela Alves; Antonelli, Lis Ribeiro do Valle; Rezende, Vitor Bortolo de; Melo, Fernanda Ludolf Ribeiro de; et al. (Frontiers in Immunology, 2022)
A panoramic analysis of chemokines, pro-inflammatory/regulatory cytokines, and growth factors was performed in serum samples from patients with acute DENV infection (n=317) by a high-throughput microbeads array. Most soluble mediators analyzed were increased in DENV patients regardless of the DENV serotype. The substantial increase (≥10-fold) of CXCL10, IL-6, and IFN- and decreased levels of PDGF (<0.4-fold) was universally identified in all DENV serotypes. Of note, increased levels of CXCL8, CCL4, and IL-12 (≥3-9-fold) were selectively observed in DENV2 as compared to DENV1 and DENV4. Heatmap and biomarker signatures further illustrated the massive release of soluble mediators observed in DENV patients, confirming the marked increase of several soluble mediators in DENV2. Integrative correlation matrices and networks showed that DENV infection exhibited higher connectivity among soluble mediators. Of note, DENV2 displayed a more complex network, with higher connectivity involving a higher number of soluble mediators. The kinetic timeline (Day 0-1, D2, D3, D4-6) analysis additionally demonstrated differences among DENV serotypes. While DENV1 triggers a progressive increase of soluble mediators towards D3 and with a decline at D4-6, DENV2 and DENV4 develop with a progressive increase towards D4-6 with an early plateau observed in DENV4. Overall, our results provided a comprehensive overview of the immune response elicited by DENV infection, revealing that infection with distinct DENV serotypes causes distinct profiles, rhythms, and dynamic network connectivity of soluble mediators. Altogether, these findings may provide novel insights to understand the pathogenesis of acute infection with distinct DENV serotypes.